Penyelesaian Goal Programming menggunakan Metode Simpleks Direvisi dalam Memaksimalkan Keuntungan pada Home Industri Upik Padang Panjang, Sumatera Barat - Syafrika Yuliarti; Muhammad Soleh; Ade Novia Rahma; Elfira Safitri; Sri Basriati (KUBIK, 2021)
Upik Home Industry is one of the businesses engaged in the chips industry. Problems in Upik Home Industry that are often faced in decision making are problems that contain several goals in it. To overcome these problems, the Goal Programming approach is used. Goal Programming is an extension of linear programming which is used to solve linear equations with more than one objective function. The purpose of this study was to determine the completion of Goal Programming using the revised simplex method in maximizing profits at Upik Home Industry Padang Panjang, West Sumatra. The method used in this study is the revised simplex method. The revised simplex method uses an inverse basis to perform calculations in determining the incoming and outgoing variables. Based on the results of research, the goal is to minimize working times, minimize raw materials for cassava, oil, salt and maximize sales quotas for sanjai balado and is not  achieved. And goals for maximizing profit,  goals for minimizing raw material for garlic and minimizing the sales quota for sanjai original, sanjai kunyit dan tusuk gigi  is achieved. So that the total production for original sanjai ( as much 30,67 kg, sanjai kunyit ( as much 18 kg and tusuk gigi ( as much 18 kg.Keywords: Goal Programming, Home industry, Revised Simplex.